Attitudes Towards Bachelor of Mountain Tourism Management (BMTM) Program Among the Students of Janapriya Multiple Campus, Pokhara - Dhakal, Rishi Ram (Janapriya Journal of Interdisciplinary Studies, 2023)
Attitude is the personal perception, beliefs and behaviour towards a particular object, person, thing or event. In psychology, an attitude refers to a set of emotion, belief, and behaviour toward a particular object, person, thing or event. The four years BMTM program is an autonomous program of JMC which is developed to serve the needs of the bright young students who have completed +2 level of education and are looking for a career education in entrepreneurship. The main objective of the study was to compare the attitude of girl and boys students toward the BMTM program of Janapriya Multiple Campus. Necessary data were collected through Likert scale questionnaire. Collected data were analyzed with mean, standard deviation, chi-square test through SPSS-20. The collected data related to students’ attitudes towards BMTM program of JMC revealed that most of the students have positive attitude towards the program. There is no difference between male and female students towards the BMTM program. Majority of students had no proper knowledge about the program. Campus administration and policy makers should concentrate on the publicity of the importance of the program for its sustainability.